Local strain distributions in partially recrystallized copper determined by in situ tensile investigation. Issue 1 (April 2015) - Lin, F X; Ubhi, H S; Petrenec, M; Zhang, Y B; Jensen, D Juul
Abstract: A partially recrystallized copper sample produced by cold-rolling and annealing was deformed in situ by uniaxial tension in a scanning electron microscope, and electron backscatter diffraction data were collected before and after deformation to certain strains. The local strain distributions are quantified using digital image correlation. Distributions of the normal strain along the tensile direction ( ε xx ) are shown in this paper. The recrystallized grains are found to deform more than the remaining unrecrystallized matrix. When ε xx is averaged along lines perpendicular to the tensile direction, significant variation are observed, which may be related to the local recrystallized volume fraction.